Determinants of Postpartum Contraception Use Among Teenage Mothers in Eastern Uganda: A Cross-Sectional Study - Muyama DL; Musaba MW; Opito R; Soita DJ; Wandabwa JN; Amongin D (Dove Medical Press, 2020)
Doreen L Muyama,1 Milton W Musaba,2 Ronald Opito,3 David J Soita,1 Julius N Wandabwa,2 Dinah Amongin4 1Department of Public and Community Health, Faculty of Health Sciences, Busitema University, Mbale, Uganda; 2Department of Obstetrics and Gynecology, Faculty of Health Sciences, Busitema University, Mbale, Uganda; 3Department of Programs, Population Services International, Kampala, Uganda; 4Department of Health Policy Planning and Management, Makerere University School of Public Health, Kampala, UgandaCorrespondence: Milton W MusabaFaculty of Health Sciences, Busitema University, Mbale, UgandaTel +256704913791Email miltonmusaba@gmail.comIntroduction: In Uganda, the proportion of women having another live birth before age 20 years (repeat adolescent birth) has not declined in 30 years. More women want to delay the next birth. We determined the prevalence and factors associated with postpartum contraceptive use among teenage mothers in Mbale City.Patients and Methods: We conducted a cross-sectional study in all the six government-supported health facilities within Mbale City. Over a period of 3 months, 511 teenage mothers in the postpartum period were consecutively enrolled by midwives/nurses. Data were collected using a pretested interviewer-administered questionnaire. We used logistic regression in STATA version 14, to determine the association between various sociodemographic characteristics and utilization of contraception. We set the level of significance at 5% and report odds ratios and the corresponding 95% confidence intervals.Results: Most of the respondents – 314/511 [61.5%, 95% CI= 57.1– 65.6%] – were using contraceptives. More than three-fourth (238/314) of the respondents opted for short-term methods of contraception. In the adjusted analyses, intention to resume school [AOR 1.79 (1.16– 2.74)], and utilization of maternal Child Heath services such as postnatal care services [AOR 0.40 (0.25– 0.63)] were significantly associated with utilisation of postpartum contraception.Conclusion: We found a high prevalence of postpartum contraceptives use – over 6 in 10 women – although they were using mainly short-term methods. Those with intentions of resuming schooling and utilised postnatal care services were most likely to use contraceptives. This is encouraging and calls for inquiry into why their use is higher than the national averages. Further, the results call for renewed efforts to maintain adolescent mothers in school.Keywords: contraceptive use, postpartum, teenage mother, Uganda, determinants